Effects of miR-1236-3p and miR-370-5p on activation of p21 in various tumors and its inhibition on the growth of lung cancer cells - Chuanchang Li; Qiangqiang Ge; Jiaxuan Liu; Qingsong Zhang; Chenghe Wang; Kai Cui; Zhong Chen (Tumor Biology)
The mechanism of dsRNA-induced gene activation (RNAa) is being gradually unveiled. The plentiful evidence that it existed in mammalian species other than human demonstrated that dsRNA-mediated RNAa is a conservative phenomenon. Simultaneously, accumulating evidence suggested that microRNAs could activate gene expression by targeting promoter. Nevertheless, it is ambiguous whether microRNA-induced gene activation in different human cells is a common phenomenon. The study we performed verified that miR-1236-3p (miR-1236) and miR-370-5p can activate p21 expression in bladder cancer (BCa) T24, EJ cells, and non-small-cell lung carcinoma A549 cells, while in hepatocellular HepG2 cells both microRNAs cannot effectively induce the expression of P21 WAF1/CIP1 (p21). In pancreatic cancer PANC-1 cells, only miR-370-5p had the potent abilities to induce p21 expression rather than miR-1236-3p. Unlike microRNA-mediated RNA activation, we can observe that dsP21-322 significantly activated p21 in above cells. Besides, we demonstrated that miR-1236 and miR-370 inhibited cyclin D1-CDK4/CDK6 pathway while upregulated E-cadherin expression by upregulation of p21 . Overexpression of these two microRNAs in A549 induced cell-cycle arrest and cell senescence, delayed cell proliferation and colony formation, and inhibited migration and invasion. In conclusion, microRNA-mediated RNAa depends on the cell context, and miR-1236 and miR-370 can inhibit non-small-cell lung carcinoma cell growth by upregulating p21 expression in vitro.